ANALISIS YURIDIS PERBANDINGAN PENGATURAN PIDANA NARKOTIKA DI INDONESIA DAN MALAYSIA - Marpiansa, Muhammad Hafizh; Pramudia, Rizki; Alfauzy, Irfan Faruq; Haikal, Muhammad; Suherman, Asep (Cahaya Ilmu Bangsa, 2025)
This study aims to analyze the comparison of narcotics criminal regulations in Indonesia and Malaysia. The main legal issue examined is the difference in legal systems in regulating narcotics crimes, particularly in terms of legal foundations, types of punishment, and approaches to offenders. The research employs a normative legal method with statutory, comparative, and conceptual approaches. The sources of legal materials include primary legal materials such as laws from both countries, secondary legal materials like journals and books, and tertiary legal materials to support the understanding of legal concepts. The results indicate that Indonesia adopts a more flexible approach by providing rehabilitation options for drug users, while Malaysia enforces stricter policies with the application of the reverse burden of proof principle and severe penalties, including the death penalty. Although Malaysia has a more repressive legal system, its effectiveness remains debatable due to the high rate of drug trafficking. Meanwhile, Indonesia faces challenges in implementing rehabilitation policies. This study recommends improving the effectiveness of the legal systems in both countries by optimizing law enforcement and considering a more balanced approach in addressing drug-related crimes. Penelitian ini bertujuan untuk menganalisis perbandingan pengaturan pidana narkotika di Indonesia dan Malaysia. Isu hukum utama yang dikaji adalah perbedaan sistem hukum dalam mengatur tindak pidana narkotika, khususnya dalam hal dasar hukum, jenis hukuman, serta pendekatan terhadap pelaku. Metode yang digunakan adalah penelitian hukum normatif dengan pendekatan perundang-undangan, perbandingan, dan konseptual. Sumber bahan hukum terdiri dari bahan hukum primer berupa undang-undang yang berlaku di kedua negara, bahan hukum sekunder seperti jurnal dan buku, serta bahan hukum tersier yang mendukung pemahaman konsep hukum. Hasil penelitian menunjukkan bahwa Indonesia menerapkan pendekatan yang lebih fleksibel dengan memberikan opsi rehabilitasi bagi pengguna narkotika, sementara Malaysia memiliki kebijakan yang lebih ketat dengan penerapan prinsip reverse burden of proof serta hukuman berat, termasuk hukuman mati. Meskipun Malaysia memiliki sistem hukum yang lebih represif, efektivitas kebijakan tersebut masih diperdebatkan karena tingginya angka peredaran narkotika. Di sisi lain, Indonesia menghadapi tantangan dalam implementasi kebijakan rehabilitasi. Studi ini merekomendasikan peningkatan efektivitas sistem hukum kedua negara dengan mengoptimalkan penegakan hukum dan mempertimbangkan pendekatan yang lebih seimbang dalam menangani peredaran narkotika.